Reasons and Promotion. Issue 1 (October 2015) - Sharadin, Nathaniel
Abstract : A number of philosophers accept promotionalism, the view that whether there is a normative reason for an agent to perform an action or have an attitude depends on whether her doing so promotes a value, desire, interest, goal, or end. I show that promotionalism faces a prima facie problem when it comes to reasons for belief: it looks extensionally inadequate. I then articulate two general strategies promotionalists can (and have) used to solve this problem and argue that, even if one of these two strategies can successfully solve the problem with reasons for belief, promotionalists face a symmetrical problem in a range of structurally similar cases. As I'll argue, the problem is that promotionalism cannot account for reasons grounded in the 'fit' between an attitude and its object. I offer an alternative to promotionalism and explain how adopting this alternative solves the problems with promotionalism while preserving much of what made promotionalism attractive in the first place.